2019
DOI: 10.1590/1413-7054201943026918
|View full text |Cite
|
Sign up to set email alerts
|

African star grass response to postemergence herbicides

Abstract: Cynodon nlemfuensis Vanderyst, commonly called African star grass, is excellent forage in pasture formation and herd feeding. However, little information is available regarding weed management in areas of star grasses. Two field experiments were carried out in 2017 and 2018 to evaluate the response of African star grass to postemergence herbicides. The treatments applied were as follows: 2,4-D (1,340.0 g ae ha-1); 2,4-D + picloram (720.0 +192.0 g ae ha-1 + 0.3% v/v nonionic surfactant); fluroxypyr + picloram (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 9 publications
(6 reference statements)
0
4
0
Order By: Relevance
“…The apparent recovery of the plant height was observed at 49 DASA for the herbicide dose of 35 + 35 g a.i. ha -1 of imazapic applied on the Tifton 419 grass (Table 4), which can be explained by the fact that nonstructural carbohydrates such as glucose, fructose, sucrose, and amides can be stored and used as reserve energy for stress tolerance and regeneration after the first symptoms of injury (Brighenti et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…The apparent recovery of the plant height was observed at 49 DASA for the herbicide dose of 35 + 35 g a.i. ha -1 of imazapic applied on the Tifton 419 grass (Table 4), which can be explained by the fact that nonstructural carbohydrates such as glucose, fructose, sucrose, and amides can be stored and used as reserve energy for stress tolerance and regeneration after the first symptoms of injury (Brighenti et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…The apparent recovery of the plants height observed at 119 DAA for the herbicide rates of 35 g ha -1 of imazapic and 15.6+5.2 g ha -1 of imazapic + imazapyr mixture in Bahiagrass (Table 4) and 105 g ha -1 of imazapic alone in Bahiagrass (Table 7) can be explained by the fact that nonstructural carbohydrates such as glucose, fructose, sucrose and amides may be stored and used as reserve energy for tolerance to stress and regeneration after the first symptoms of injury (Brighenti et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…ha -1 ), and atrazine + tembotrione (1,000.0 + 100.8 g i.a. ha -1 + 0.3% v/v mineral oil) applied to postemergence African Bermuda grass (Cynodon nlemfuensis Vanderyst) in the state of Minas Gerais, Brighenti, Benites and Souza Sobrinho (2019) found that the most phytotoxic treatments for the species were fluroxypyr + amininopyralid, fluroxypyr + triclopyr, and atrazine + tembotrione, with a reduction of approximately 35, 23, and 55%, respectively, for the variable dry matter of plants. The researchers also commented that the dry matter yield of African Bermuda-grass plants was not affected by the application of 2,4-D, 2,4-D + picloram, bentazon, imazapyr, MSMA, and atrazine + S-metolachlor, and these herbicides could be considered potential treatments in the management of African Bermuda-grass pastures.…”
Section: Selectivitymentioning
confidence: 99%